Estudo da ação da toxina botulínica do tipo A na profilaxia da migrânea sem aura - D’Almeida, José Artur Costa (2004)
A randomized, double-blind, placebo-controlled study of the use of botulinum toxin type A in the prophylactic treatment of Migraine is presented. Migraine is a common type of primary, benign, episodic headache. It is characterized by pain usually unilateral and throbbing. Other associated symptoms are nausea, sensitivity to light and sound, or irritability. The pain is usually worsened by physical activity. There are also motor, sensitive, or visual neurological alterations, denominated aura. The physiopathology of migraine is not still perfectly understood but it could involve liberation of vasoactive neuropeptides as Substance P, Neurokinine A, and Calcitonin gene-related peptide, promoting an inflammation. Migraine, then, would be the result of a complex process that would involve the brainstem and induce local inflammation of cranial blood vessels. In spite of the therapeutic options (analgesics, steroidal and non-steroidal anti-inflammatory, triptans, neuroleptics, ergot derivatives, and opioids) only about one third of patients is satisfied with the treatment. The preventive treatment is appropriate for those that have frequent crises. It was observed that the patients using botulinum toxin for aesthetic treatment of wrinkles of the face, or dystonia presented a reduction in the amount of migraine crises. The botulinum toxin is a potent neurotoxin produced by the bacterium Clostridium botulinum. The action of the toxin is to inhibit the acetylcholin liberation from the nerve terminal. It acts also inhibiting the liberation of vasoactive neuropeptides. Therefore, Botulinum Toxin would act exactly in the core of the physiopathologic process of the disease. With the objective of testing possible analgesic effects of botulinum toxin in migraine without aura bearers, we performed a double-blind, controlled, and randomized study. The pain level was measured by scales and by the amount, and number of days of pain in a week, before and after botulinum toxin’s injection in muscles of the face. The placebo group received saline injection. The patients were followed for three months. At the end it was concluded that there was not statistic difference in intensity nor in frequency of the headache of the patients that used botulinum toxin in relation to the people that used placebo (saline).